Bioinspired Strong, Tough, and Biodegradable Poly(Vinyl Alcohol) and its Applications as Substrates for Humidity Sensors. Issue 7 (29th January 2023) - Liu, Lei; Xu, Xiaodong; Zhu, Menghe; Cui, Xihua; Feng, Jiabing; Rad, Zahra Faraji; Wang, Hao; Song, Pingan
Abstract: Biodegradable polymeric materials with high strength and outstanding toughness are necessary for real‐world applications in the fields of electronics, electrics, and packaging. Unfortunately, such performance portfolios in polymers remain challenging to achieve due to their different governing mechanisms. Inspired by the hydrogen‐bond (H‐bond) cross‐linking structure of spider silk, herein, strong and tough poly(vinyl alcohol) (PVA) composites with β‐cyclodextrin as a cross‐linker are developed. Benefiting from the H‐bond cross‐linking effect, the addition of 1.0 wt% of β‐cyclodextrin enables PVA to achieve a high tensile strength of 136.5 MPa, and a high elastic modulus of 3.0 GPa, in combination with a good toughness of 82.1 MJ m −3 . In addition, the presence of β‐cyclodextrin improves the biodegradability of PVA composite by decreasing its crystalline size. Furthermore, PVA/β‐cyclodextrin composite combined with MXene has great potential as a sensor material for humidity and strain detection. This proof‐of‐concept opens numerous opportunities to create strong, tough, and biodegradable polymers for packing and sensing applications. Abstract : Inspired by the nanoconfinement effect of β‐sheet crystalline in spider silk, nanostructured PVA composite film is developed by using β‐cyclodextrin molecule as a cross‐linker. As‐fabricated polymer nanocomposite film exhibits high strength, great toughness, and good biodegradable performances, which hold great promise for humidity and strain sensors by combining MXene nanosheets.